2022
DOI: 10.3390/foods11244068
|View full text |Cite
|
Sign up to set email alerts
|

Sour Beer with Lacticaseibacillus paracasei subsp. paracasei F19: Feasibility and Influence of Supplementation with Spondias mombin L. Juice and/or By-Product

Abstract: This study aimed to evaluate the probiotic strain Lacticaseibacillus (L.) paracasei subsp. paracasei F19 (F19) with the yeast Saccharomyces cerevisiae US-05 (US-05), using Spondias mombin L. (‘taperebá’ or ‘cajá’) juice and by-product, in four sour-type beer formulations: control, with bagasse, juice, and juice and bagasse. The viability of F19 was evaluated by pour-plating and PMA-qPCR. Fermentability, in addition to physicochemical and sensory parameters, and aroma and flavor, were evaluated during brewery b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…The three strains ( L. rhamnosus LGG, B. infantis BB‐02 and S. thermophilus TH‐4) exhibited considerable growth in the negative controls, i.e., in m‐MRS without supplementation, indicating their capability to adapt to a carbohydrate‐free environment and obtain energy from other sources. The same behaviour was reported for L. paracasei F19 (Praia et al ., 2022). Conversely, no significant folate production was observed in these negative controls, highlighting the effect of the tested substrates on folate production.…”
Section: Resultsmentioning
confidence: 99%
“…The three strains ( L. rhamnosus LGG, B. infantis BB‐02 and S. thermophilus TH‐4) exhibited considerable growth in the negative controls, i.e., in m‐MRS without supplementation, indicating their capability to adapt to a carbohydrate‐free environment and obtain energy from other sources. The same behaviour was reported for L. paracasei F19 (Praia et al ., 2022). Conversely, no significant folate production was observed in these negative controls, highlighting the effect of the tested substrates on folate production.…”
Section: Resultsmentioning
confidence: 99%
“…The L. paracasei subsp. paracasei (F19) strain has the interesting characteristics of genetic stability throughout production [ 21 , 22 , 23 ], survival in digestive conditions, beneficial interaction with the intestinal epithelium, and changes in host nutrient utilization and energy metabolism [ 39 ]. Other evidence from clinical studies summarized by Jones [ 40 ] corroborates more positive claims of L. paracasei F19 associated with a high-fiber diet in improving swelling and abdominal pain, as well as the influence of this probiotic in reducing the accumulation of fat by modulating transcription factors in energy metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…As expected, there was an increase in total fiber content and, mainly, insoluble fiber content in the Test Formulation (TF) compared with the Control Formulation (CF) ( p < 0.05) ( Table 4 ). It can be expected that the microbial enzymatic metabolism acts on this added matrix, favoring the production of new derived compounds with an impact on aroma and functionality during fermentation and storage [ 21 , 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been demonstrated that probiotic strains of Lacticaseibacillus paracasei subsp. paracasei F19 [12,13] and 431 [13] are strong contenders for utilization in sour beer production, given their impressive survival rates. However, these studies used normal amounts of hops, typically, not exceeding 10 International Bitterness Units (IBU).…”
Section: Introductionmentioning
confidence: 99%